The Relationship between Optimism and Mindfulness with Cognitive Performance in Older Adults - Sanaz Ghannadi; Morteza Tarkhan (Journal of Modern Psychology)
Objective: Aging and the onset of old age are accompanied by inevitable changes in cognitive function. Therefore, considering the aging population and the importance of cognitive functions during this sensitive age period, identifying factors affecting cognitive function to enhance their cognitive abilities deserves attention. The present study aimed to investigate the relationship between optimism and mindfulness with cognitive function in older adults.Methods: The present research employed a descriptive and correlational design. The statistical population of the study included all older adults residing in nursing homes in Guilan Province in the year 2020-2021. The study sample consisted of 160 older adults who were selected from residents of nursing homes using purposive sampling. The research instruments included the Revised Life Orientation Test (LOT-R) for optimism, the Five Facet Mindfulness Questionnaire (FFMQ) for mindfulness, and the Cognitive Performance Evaluation Questionnaire (CPEQ) for cognitive function. Data were analyzed using Pearson's correlation coefficient and multiple regression analysis (simultaneous method) at a significance level of 0.05.Results: The results showed a significant positive relationship between optimism and mindfulness with cognitive function, meaning that the more optimistic and mindful older adults were, the better their cognitive function. Furthermore, 34% of the variance in cognitive function was explained by optimism and mindfulness.Conclusion: Therefore, based on the findings of the present study, it can be concluded that optimism and mindfulness are important variables in predicting cognitive function (p < 0.05).